Measuring provider well-being: initial validation of a brief engagement survey - Megan Call; Fares Qeadan; Benjamin Tingey; Ellen Morrow; David Webber; Blake Hamilton; Amy Locke (BMC, 2023)
Abstract Background Measurement is one of the critical ingredients to addressing the well-being of health care professionals. However, administering an organization-wide well-being survey can be challenging due to constraints like survey fatigue, financial limitations, and other system priorities. One way to address these issues is to embed well-being items into already existing assessment tools that are administered on a regular basis, such as an employee engagement survey. The objective of this study was to assess the utility of a brief engagement survey, that included a small subset of well-being items, among health care providers working in an academic medical center. Methods In this cross-sectional study, health care providers, including physicians and advanced clinical practitioners, employed at an academic medical center completed a brief, digital engagement survey consisting of 11 quantitative items and 1 qualitative item administered by Dialogue™. The emphasis of this study was on the quantitative responses. Item responses were compared by sex and degree, domains were identified via exploratory factor analysis (EFA), and internal consistency of item responses was assessed via McDonald's omega. Sample burnout was compared against national burnout. Results Of the 791 respondents, 158 (20.0%) were Advanced Practice Clinicians (APCs), and 633 (80.0%) were Medical Doctors (MDs). The engagement survey, with 11 items, had a high internal consistency with an omega ranging from 0.80-0.93 and was shown, via EFA, to have three domains including communication, well-being, and engagement. Significant differences for some of the 11 items, by sex and degree, in the odds of their agreement responses were found. In this study, 31.5% reported experiencing burnout, which was significantly lower than the national average of 38.2%. Conclusion Our findings indicate initial reliability, validity, and utility of a brief, digital engagement survey among health care professionals. This may be particularly useful for medical groups or health care organizations who are unable to administer their own discrete well-being survey to employees.